Functional characterization of Magnaporthe oryzae (anamorph. Pyricularia oryzae) effector during infection - Paula, Samuel de (2024)
The filamentous ascomycete fungus Magnaporthe oryzae (syn. Pyricularia oryzae) represents a critical challenge to global food security due to its role in causing devastating blast diseases in rice. These diseases account for yield losses estimated at 1030% of total global rice production. M. oryzae utilizes a sophisticated arsenal of effectors to circumvent the innate immune defenses of the host and successfully invade plant cells. These effectors are specialized proteins that interact with the host\'s cellular mechanisms, manipulating them to facilitate infection and proliferation of the pathogen. The primary objective of this study was to provide a comprehensive review on M. oryzae and to augment the characterization of the M. oryzae effector Bas83 and to assess its impact on the symptomatology of rice blast disease. In order to elucidate the role of the Bas83 effector in the infection dynamics and progression of the blast fungus, the research utilized the M. oryzae Guy11 wild-type (WT) strain. This study employed a dual approach in genetic manipulation, incorporating both overexpression and RNA interference (RNAi)-mediated gene silencing techniques. These methodologies were strategically chosen to provide a comprehensive understanding of Bas83\'s functional roles within the infection process, offering insights into how its modulation affects disease manifestation in rice. Additionally, the study investigated the role of specific protein domains in Bas83 in dictating the effector\'s localization and secretion dynamics within host cells. This was achieved through a targeted protein domain deletion approach, allowing for a detailed assessment of how particular domains influence the spatial distribution and functional activity of Bas83 in the host-pathogen interaction process. This study failed to produce Bas83:mRFP overexpression strains but successfully generated three strains with notable Bas83 silencing (68%, 69%, and 79%). These strains showed a direct impact on infection stages compared to the Guy11 WT. In planta assays indicated that RNAiBas83 strains had lower disease scores (2-3) versus the Guy11 WT (4-5), confirming Bas83\'s significant influence on blast disease development. Also, the findings show that domain deletions in the Bas83 protein markedly alter its localization and secretion into the biotrophic interfacial complex (BIC) of M. oryzae. While the intact Bas83 protein tagged with mRFP accumulates into the outlayers of BICs, the deletions of the secretion signal (SS) and amino acid sequences 22-61, 62-120, and 121-173 blocked their secretion into BICs, leading to their accumulation into fungal invasive hyphae. In conclusion, the silencing of Bas83 significantly impacts the infection stages of M. oryzae and the progression of blast disease. Additionally, the deletion of putative protein domains in Bas83 influences the effector\'s localization and secretion through the BICs.